The Driver Behaviour and Impact of Speed on Road Safety on the Motorways in Croatia - Zovak, Goran; Kos, Goran; Huzjan, Boris (Promet - Traffic&Transportation, 2017)
The paper presents the current research related to the speed of traffic flow on the roads of high serviceability. It analyses the speed of vehicle as one of the main causes of traffic accidents. A flat four-lane motorway section, motorway section in the tunnel and a city bypass section were chosen for this research, and several speed limit scenarios for the vehicles have been applied with the aid of variable signalling. The survey results show that few vehicles respect the speed limits in traffic in the case of a straight section of motorway or city stretch of the motorway which has good geometric elements; however, speed limits are exceptionally well respected in tunnels. Although a large number of drivers do not respect the signs, a certain group of drivers can be influenced by variable signs of limitations, and thus positive changes can be achieved in traffic flow which will result in increasing the traffic safety on the motorways. Thus, increasing the degree of respect for speed limits on the motorways directly affects the increase in the level of traffic safety. It is necessary to influence the group of drivers who do not respect the speed limits with other measures, including repressive ones.